A Patterns-Based Model to Transfer Objects Between Object-Oriented Application - Tran Dan Thu (Journal of Technical Education Science, 2007)
The communication between several applications is an important issue for modern software. Communication protocols are available with many function libraries in support of developing network applications. However, the programming interfaces of communication libraries yield source code fragments to be difficult to reuse because of code duplication or hard coding. Furthermore, database systems also support developers to implement communication functions at a high level. But database systems are only adequate to the development of software systems in which the data storage or administration is most important. In this paper, we propose a light-weight model to give the capability of transferring objects between applications to be implemented in object-oriented programming languages. To realize this model, we apply certain design patterns in designing principal classes to transfer objects from an application to another. A prototype implementation of this project has been developed in C++ as open source.